Variation in stress distribution modified by mandibular material property: a 3D finite element analysis. (February 2023) - Zheng, Fangjie; Zhu, Yunfan; Gong, Yanji; Yin, Deqiang; Liu, Yang
Highlights: Developed a 3D finite element model to describe the human maxillofacial system. Discussed the influence of material property of mandibular bone on stress distribution of TMJ. Discussed the effect of structural asymmetry on distinct trends between left and right sides. Determined the favorable material modelling in finite element analysis Abstract: Background: Temporomandibular joint disorder (TMD) is a common oral and maxillary facial disease. Finite element method (FEM) has been widely used in TMD studies. Material assignment significantly affects FEM results. The differences in the methods of material assignment used in previous studies have not been comprehensively assessed for further calculations. Methods: The mandible material modelling approaches were of four types, namely: uniform modelling with (A) cortical bone; and (B) cancellous bone; (C) semi-uniform modelling with division of cortical and cancellous bone; and (D) non-uniform modelling with Computed tomography (CT) gray value related modulus. Meanwhile, the Young's modulus of values ranging from 20 to 300 GPa were considered for the teeth. Ten modellings were used to analyze and discuss the differences in contact pressure and contact force. Results: (1) The increase in teeth elastic modulus increased the maximum contact pressure on the alveolar bone and contact force on teeth, but induced insignificant stress variation on the temporomandibular joint; (2) The location of the maximum contact pressure was steady for all four modelling approaches of the mandibular material. However, the maximum contact pressure and contact force exhibited an insignificant difference. Conclusions: Teeth with a higher elastic modulus significantly enhanced the stress concentration in the alveolar bone; in contrast, it induced minor variations in the temporomandibular joint stress states. The extreme stress regions predicted by the four mandibular models were consistent with the actual damaged regions. However, non-uniform modellings based on CT values could better describe the mechanical properties of the human bone, which should be primarily considered. Graphical abstract: Image, graphical abstract